FBXO34 Regulates the G2/M Transition and Anaphase Entry in Meiotic Oocytes - Zhao, Bing-Wang; Sun, Si-Min; Xu, Ke; Li, Yuan-Yuan; Lei, Wen-Long; Li, Li; Liu, Sai-Li; Ouyang, Ying-Chun; Sun, Qing-Yuan; Wang, Zhen-Bo (Frontiers in Cell and Developmental Biology, 2021)
There are two important events in oocyte meiotic maturation, the G2/M transition and metaphase I progression. Thousands of proteins participate in regulating oocyte maturation, which highlights the importance of the ubiquitin proteasome system (UPS) in regulating protein synthesis and degradation. Skp1–Cullin–F-box (SCF) complexes, as the best characterized ubiquitin E3 ligases in the UPS, specifically recognize their substrates. F-box proteins, as the variable adaptors of SCF, can bind substrates specifically. Little is known about the functions of the F-box proteins in oocyte maturation. In this study, we found that depletion of FBXO34, an F-box protein, led to failure of oocyte meiotic resumption due to a low activity of MPF, and this phenotype could be rescued by exogenous overexpression of CCNB1. Strikingly, overexpression of FBXO34 promoted germinal vesicle breakdown (GVBD), but caused continuous activation of spindle assembly checkpoint (SAC) and MI arrest of oocytes. Here, we demonstrated that FBXO34 regulated both the G2/M transition and anaphase entry in meiotic oocytes.